A Look Back: Kappan authors on desegregation. (February 2019) - Preston, Teresa
The Kappan archives offer a window into education history as it happens, a fact that is especially clear when it comes to the issue of segregation. In this column, Teresa Preston traces the history of how educators and scholars have debated in Kappan whether schools should desegregate, how desegregation laws should be enforced, and what sorts of actions are appropriate in furthering the cause of equality .